Redução de lead time em ambiente de fabricação sob encomenda por meio da abordagem Quick Response Manufacturing (QRM) - Chinet, Fernanda Silva (2014)
In the latest decades, companies have faced important and increasing challenges set by globalization in product markets and production factors. This way, consumers become highly demanding and are always searching for new products, highly qualified, customized and quickly produced. Given these changes, the speed of delivery and therefore the efforts to reduce lead time emerges as one of the main objectives adopted by a company to compete in the market, since the strategies based in time aim to provide faster answers to its customers. In this context, the present paper aims to describe a proposal to reduce the lead time from the application of the concepts and methodology tools Quick Response Manufacturing (QRM) in a capital good sector s company. In order to achieve the proposed objective, a literature review about the QRM methodology and POLCA system and a case study in a company that develops and manufactures machinery and custom made equipment. Thus, it was analyzed the main causes of the waiting in the manufacturing of pressure vessels process, and through improvement proposals, it was achieved the results and gains expected. The main results, other than the 40% reduction in lead time, are related to quality improvement, increase of process responsibility in the manufacturing and simplifying the production control.